Beliefs, Facilitating Factors, and Barriers in Using Personal Dosimeter among Medical Radiation Workers in a Middle-Income Asian Setting. Issue 8 (25th May 2021) - Mohd Ridzwan, Siti Farizwana; Bhoo-Pathy, Nirmala; Wee, Lei Hum; Isahak, Marzuki
Abstract: This qualitative study explores the medical radiation workers' (MRWs) beliefs with the support of the theory of planned behaviour's constructs regarding the use of personal dosimeters in order to identify the facilitating factors and barriers to practising good personal dose monitoring. The exploration was conducted through semi-structured face-to-face interviews with 63 MRWs from the public, private, and university hospitals. Belief statements from the informants were organized under the behavioural, normative, and control belief, as guided by the theory. A thematic analysis found that a majority of informants acknowledged the benefits of using dosimeters. However, several factors influenced the actual usage. The informants were hesitant to use the dosimeter as the loss of the device involved an expensive penalty. They also mentioned that delayed dosimeter supplies due to late budget approval in the hospitals and some other reasons had got them disconnected from the monitoring system. The workers' attitudes and social norms highly induced their dosimeter usage as well; some perceived themselves to be at low risk for high exposure to radiation, and forgetfulness was also mentioned as a reason for lack of adherence. Device physical factor influenced low dosimeter use too. This study highlighted some unique findings in Asian settings. A better understanding of the underlying reasons for the lack of dosimeter use will be useful in developing strategies to increase good practices in personal radiation monitoring.